The role of socialization institutions in influencing the behavior of children who survived the earthquake "Study of a number of cases in Al-Asaliyah neighborhood " - أحمد, دارين; ميرنا دلالة (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The current research aims to identify the role of socialization institutions in influencing the behavior of children who survived the earthquake of February 6, 2023 in the city of Jableh. The case of ten children in the Al-Assaliyah neighborhood was studied, by interviewing them, and observation was used as a study tool. The children's families and teachers were also consulted to clarify any inquiries the researcher had. The results showed: 1- It appeared through the case study that half of the respondents showed symptoms of recurrence, which are recalling memories of the earthquake, followed by neurological symptoms and academic difficulties to a lesser extent, and then avoidance symptoms. 2- It was found that neurological symptoms and psychosomatics symptoms disappeared a few days after the earthquake, meaning that they were transient, and their disappearance was associated with engaging in activities and social participation with peers, and they were controlled within a short period after the earthquake for all ages and both sexes. 3- It was found that recurrence symptoms may arise in a child due to the psychological state of his parents and his viewing of images of the disaster on the media. 4- It was found that the symptoms of avoidance are linked to the frightening conversations circulating within the family about stories of the earthquake disaster.